Study on the Influencing Factors of Direct Current Dipole Array for Tunnel Advance Detection and Its Application - Xiaozhen Teng; Jianhua Yue; Shuanggui Hu; Chao Sun; Kailiang Lu; Herui Zhang; Danyang Xi (IEEE Access)
The direct current resistivity method is a primary technique for detecting water-bearing structures ahead of tunnel and coal mine excavation faces. We propose a dipole array advance detection device based on the DC method, and quantified the advance detection effect and the optimum device parameters using numerical simulation, and then verified it on field application. Firstly, the corresponding methods for data gathering and processing are introduced. Then, according to simulation of several geoelectric models, we optimized the device parameters on the detection effectiveness, such as the current electrode numbers, electrode spacing, the shape and position of the anomalous body. The optimal device parameters are then selected based on these considerations. Using the optimized parameters, we finally conducted a field test to obtain the electrical response characteristics ahead of the tunneling face, and the results were validated with the transient electromagnetic method. The device successfully detects low-resistance anomalies at distances of 20 to 50 m ahead of the tunnel face, validated by borehole drilling. It illustrates that the dipole array advance detection device can at least detect low-resistance anomalies up to 40 m ahead of the tunneling face, with an electrode spacing of 4 m and four current electrodes. The device’s high detection accuracy and construction efficiency significantly reduce labor and material costs in field applications, offering both theoretical and practical value.